Efektivitas Ekstrak Bawang Putih (Allium sativum) Terhadap Mortalitas Larva Aedes aegypti : The Effectiveness of Garlic Extract (Allium sativum) Against the Mortality of Larvae Aedes aegypti - Agesti, Eka Fauzia; Wardani, Dita Pratiwi Kusuma; Mujahid, Ikhsan; Hikmawati, Isna (Perkumpulan Entomologi Kesehatan Indonesia, 2025)
Aedes aegypti is a dengue fever vector that can transmit dengue (DEN-V). Pyrethroid, carbamate, and organophosphate synthetic insecticides are often used as dengue control because they are very effective, quick to show results, and have minimal environmental impact. Garlic is commonly used as a seasoning by some people, but this plant has potential as an alternative larvicide. This plant contains the compounds allicin, sulfur ammonia acid, and allin. This study aims to determine the larvicidal effect of garlic extract on the mortality of Ae. aegypti larvae. The study was conducted with a post-test with a control group design of 5 groups. There are two groups: a negative control group (Aquadest) and a positive control (Temefos 1%). The other three groups were treated with garlic extract concentrations of 10% (P1), 20% (P2), and 30% (P3). There were 375 Ae. aegypti larvae with 3 repetitions, and 24 hours of larval mortality were observed. The Kruskal-Wallis and post hoc Mann-Whitney U tests analyzed larval mortality data. LC50 and LC90 values were subjected to probit analysis. The results of the Kruskal-Wallis test showed that there were differences in the effectiveness of garlic extracts on the mortality of Ae. aegypti larvae (p = 0.007). The LC50 value is 2.346%, while the LC90 value is 2.641%. Garlic extract (Allium sativum) is effective as a larvicide for Ae. aegypti